Conflicts between reindeer herding and an expanding caribou herd in Alaska - Finstad, Greg L.; Bader, Harry R.; Prichard, Alexander K. (Rangifer, 2002)
The reindeer industry has existed in Alaska since 1892. This industry has largely been concentrated on the Seward Peninsula, Alaska because suitable habitat has been available and caribou have been absent here for over 100 years. Until recently, reindeer meat and velvet antler production consistently generated millions of dollars in revenue critical to the economies of rural Alaskan communities. From 1976 to 1996 the Western Arctic Caribou Herd (WACH) increased from about 75 000 to 463 000 animals. Concurrently, seasonal range use of the WACH shifted westward onto traditional reindeer ranges of the Seward Peninsula. Reindeer herders lost 75-100% of their herds through commingling and out¬migration with wild caribou. This loss of over 12 000 reindeer represents a potential economic value of 13 million dollars. Sustainable meat and velvet antler production and the economies of western Alaskan are likely to be affected by these changes.